Compatibility of language use in school level textbooks - Ramasamy, K; Ramamani (Mysore : Central Institute of Indian Languages, 1986)
Study conducted on the textbooks prescribed in the schools in Karnataka State.
Bibliography: p. 265.
English
Keywords: Textbooks -- India -- Karnataka